2021
DOI: 10.3390/su13158228
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Sustainable Operation of Low-Carbon Tourism Supply Chain under Sudden Crisis Prediction

Abstract: This paper integrates a low-carbon tourism supply chain consisting of a low-carbon tourist attraction (LTA) providing a low-carbon service and an online travel agency (OTA) responsible for big data marketing. Consumers may also encounter sudden crisis events that occur in the tourist attraction during their visit, and the occurrence of crisis events can damage the low-carbon goodwill of the tourist attraction to the detriment of the sustainable development of the supply chain. Therefore, this paper aims to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…• Others include decision-making trial and evaluation laboratory (DEMATEL) (Miao et al 2014 ), Delphi (von der Gracht and Darkow 2013 ), dynamic programming (Zhang et al 2021 ), entropy analysis (Lu et al 2019 ), equilibrium displacement model (Xiao 2010 ), event sequence analysis (Sprecher et al 2017 ), fault tree analysis (Kumar and Havey 2013 ), failure mode, effects, and criticality analysis (FMECA) (Raab et al 2013 ), flow modelling (Lehmann et al 2011 ), fuzzy quality function deployment (Tamtam and Tourabi 2021 ), genetic algorithm and multi-choice goal programming (Razavi et al 2021 ), inductive case-based reasoning ensemble (ICBRE) (Li et al 2012 ), Petri-nets (Wang et al 2016 ), Pugh matrix approach and Monte Carlo simulation (Baležentis et al 2021 ), and Theory of Constraints (Yang et al 2009 )…”
Section: Resultsmentioning
confidence: 99%
“…• Others include decision-making trial and evaluation laboratory (DEMATEL) (Miao et al 2014 ), Delphi (von der Gracht and Darkow 2013 ), dynamic programming (Zhang et al 2021 ), entropy analysis (Lu et al 2019 ), equilibrium displacement model (Xiao 2010 ), event sequence analysis (Sprecher et al 2017 ), fault tree analysis (Kumar and Havey 2013 ), failure mode, effects, and criticality analysis (FMECA) (Raab et al 2013 ), flow modelling (Lehmann et al 2011 ), fuzzy quality function deployment (Tamtam and Tourabi 2021 ), genetic algorithm and multi-choice goal programming (Razavi et al 2021 ), inductive case-based reasoning ensemble (ICBRE) (Li et al 2012 ), Petri-nets (Wang et al 2016 ), Pugh matrix approach and Monte Carlo simulation (Baležentis et al 2021 ), and Theory of Constraints (Yang et al 2009 )…”
Section: Resultsmentioning
confidence: 99%
“…The results of the value chain analysis of the operational process show that one of the keys to the success of Dato Beach as a tourist destination lies in good and professional management. It can be seen that previous research found that good governance lies in the sustainable operation of the tourism supply chain in anticipating the tourist attraction crisis (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…The beneficial role of carbon options in carbon asset management and investment decision-making has been demonstrated. Zeng [29] pointed out that carbon options can achieve Pareto improvement in the supply chain and improve social welfare. Compared to other financial products, carbon options may be a product that brings profits to multiple participants.…”
Section: Carbon Options and Corporate Profitsmentioning
confidence: 99%